The mediating effect of Educational Decentralization in the Relationship between Citizen Participation and Education Service Delivery of Local Governments - Twinomujuni, Rosebell; Mawa, Michael; Buwule Musoke, Henry; Rukanyangira, Nazarious (International Journal of Innovative Science and Research Technology, 2022)
The current study was broadly undertaken to investigate the effect of educational decentralization on the fit citizen participation and education service delivery in selected Local Governments in Uganda. The results indicated a moderate level of Education Service Delivery in Ugandan Local Governments (M =2.74, SD = 1.095) with a statistically significant negative influence of nominal participation on education service delivery (β = -0.514, p < 0.001). Results also showed instrumental participation has got a statistically significant positive influence on Education decentralization (β = 0.299, p<0.001) with administrative decentralization has a negative significant influence on education service delivery (β = -0.264, p = 0.003 < 0.05). The study concluded a generally less than satisfactory level education service delivery and instrumental participation as a form of citizen participation remains crucial but with appropriate integration of administrative decentralization. It was thus recommended among others that the Ministry of Education and Sports in collaboration with local educational authority should develop and institutionalize strategies that periodically strengthen powers of local authorities to allocate financial resources and as well develop regulatory controls in public educational institutions for enhanced education service delivery.
Keywords: mediating effect; Educational Decentralization; Education Service; Citizen Participation